Digital Transformation and Tax Compliance: A Literature Study on the Impact of E-Filing on the Taxation System - Fatikhah Romadhona; Ana Farida Sahara; Yananto Mihadi Putra (Baca Dulu Publisher, 2025)
Digital transformation has become a global phenomenon that significantly impacts various sectors, including Indonesia’s tax system. The implementation of the e-filing system allows taxpayers to report taxes online without having to visit tax offices, thereby accelerating, facilitating, and increasing transparency in the tax reporting process. This study examines the effect of e-filing on taxpayer compliance using compliance data and the number of registered taxpayers from 2021 to 2023. The results indicate that the compliance rate among e-filing users increased from 84.07% in 2021 to 86.97% in 2023. Beyond easing tax reporting obligations, the system also contributes to enhancing state revenue and expanding the taxpayer base. These findings confirm that digital transformation through e-filing is an effective solution for improving the efficiency of tax in Indonesia.